Fuzzy due-date scheduling problem with fuzzy processing time - Itoh, T.; Ishii, H. (International transactions in operational research, 1999)
For most of scheduling problems, jobs' processing times and due‐dates are treated as certain values, but that is not proper to all actual situations. Processing times are not constant because of measurement errors in the data sets for deciding them and/or human actions in the manufacturing process. However, we may be permitted to exceed due‐dates slightly. In this paper, we propose a model dealing with uncertain processing times and flexible due‐dates in consideration of real situations. Assuming the times and due‐dates to be fuzzy numbers, and defining a fuzzy tardiness for a job's due‐date, we design to minimize the number of tardy jobs in our problem formulation.